2017
DOI: 10.1371/journal.pone.0189380
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Receptor 3 negatively regulates oligodendrocyte differentiation and remyelination

Abstract: BackgroundAgents promoting oligodendrocyte precursor cell differentiation have the potential to restore halted and/or delayed remyelination in patients with multiple sclerosis. However, few therapeutic targets have been identified. The objective of this study was to identify novel targets for promotion of remyelination and characterize their activity in vitro and in vivo.MethodsA high-content screening assay with differentiation of primary rat oligodendrocyte precursor cells was used to screen GSK-proprietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Histamine, which is encoded by the HDC enzyme, has been demonstrated to be involved in cell proliferation, embryonic development, and tumor growth [12,[43][44][45]. However, its roles in cardiac differentiation and heart development have not been given enough attention over the past decades.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine, which is encoded by the HDC enzyme, has been demonstrated to be involved in cell proliferation, embryonic development, and tumor growth [12,[43][44][45]. However, its roles in cardiac differentiation and heart development have not been given enough attention over the past decades.…”
Section: Discussionmentioning
confidence: 99%
“…This H3-receptor antagonist was originally developed to treat Alzheimer’s disease [ 111 , 112 ] and was put forward as a potential remyelinating agent because H3 negatively regulates oligodendrocyte differentiation [ 113 ]. A phase 2, randomised, placebo-controlled study in people with RRMS on interferon or glatiramer acetate revealed a small, but significant, improvement in mean change in post-lesion MTR in gadolinium-enhanced lesions compared to placebo [ 114 ].…”
Section: Remyelination Clinical Trialsmentioning
confidence: 99%
“…Furthermore, the antifungal agent miconazole, which interferes with ergosterol synthesis, as well as corticosteroid betamethasone clobetasol, which suppresses inflammatory responses, were demonstrated as therapeutic compounds for enhancing (re)myelination in vivo and in human OPCs in vitro [128]. Moreover, modulation of histamine receptor signaling by means of GSK239512, a histamine H3 receptor antagonist, was demonstrated to boost oligodendroglial differentiation as indicated by phenotypic screening and genetic association of human demyelination lesion samples of patients with MS [129]. In this regard, magnetization transfer ratio (MTR)-based post-hoc analyses indicated a small mean improvement in myelin content in treated patients with relapsing remitting (RR) MS relative to placebo [130].…”
Section: Regulators Of Glia Cell Fate: Avenues To Adjust Aberrant Whimentioning
confidence: 99%